Analysis of the impact of caregiver training program intervention on frailty in colon cancer patients undergoing postoperative chemotherapy - Nie Tingting; Zhang Wei; Li Yuanyuan; Zhao Tianxue (结直肠肛门外科)
[Objectives] To explore the impact of caregiver training program intervention on frailty in colon cancer patients undergoing postoperative chemotherapy. [Methods] A retrospective analysis was conducted on the clinical data of 104 colon cancer patients who received postoperative chemotherapy in our hospital from March 2021 to April 2022. These patients were recruited to investigate the effectiveness of the caregiver training program intervention. Based on the interventions received during postoperative chemotherapy, they were divided into a control group and an observation group. The control group received conventional chemotherapy nursing and standard frailty prevention and management for colon cancer patients. The observation group received additional caregiver training program intervention. Each group included 52 patients who met the research requirements. The intervention period lasted for 6 months, from the beginning of the first chemotherapy session to the end of the total chemotherapy course. The frailty status of the patients was assessed using the Fried frailty phenotype scale and the Comprehensive Frailty Assessment Instrument (including physical frailty, psychological frailty, social frailty, and environmental frailty dimensions) before the first chemotherapy session (pre-intervention) and after the total chemotherapy course (post-intervention). The frailty scores before and after the intervention were compared. [Results] For the Fried frailty phenotype scale: before the intervention, there was no statistically significant difference in scores between the two groups (P>0.05). After the intervention, the observation group had significantly lower scores than the control group, while the control group had significantly higher scores than before the intervention (P<0.05). There was no statistically significant difference in scores before and after the intervention in the observation group (P>0.05). For the Comprehensive Frailty Assessment Instrument: before the intervention, there were no statistically significant differences in scores for each dimension and the total score between the two groups (P>0.05). After the intervention, the observation group had significantly lower scores for each dimension and the total score compared to the control group (P<0.05). The control group had significantly higher scores for each dimension and the total score compared to before the intervention (P<0.05). In the observation group, the score for the physical frailty dimension after the intervention was significantly higher than before the intervention (P<0.05), while there were no statistically significant differences in scores for the other dimensions and the total score before and after the intervention (P>0.05). [Conclusion] For colon cancer patients undergoing postoperative chemotherapy, adding caregiver training program intervention to conventional chemotherapy nursing and standard frailty prevention and management for colon cancer patients could help delay the worsening of frailty during chemotherapy.